Variable facial plumage in juvenile Cliff Swallows: A potential offspring recognition cue?. (5th February 2014) - Johnson, Allison E.; Freedberg, Steven
Abstract: Although the ability to recognize related offspring is essential in the evolution of social behavior, the cues that birds use to identify their own offspring are not fully understood. The Cliff Swallow ( Petrochelidon pyrrhonota ) is a highly social species that nests in large colonies and exhibits a high incidence of both conspecific brood parasitism and extrapair fertilization, behaviors that can potentially lead to parents investing energy and resources in unrelated offspring, which reduces the parents' genetic fitness. Because parents continue to feed offspring after they leave the nest, parents also risk investing in unrelated offspring by misidentifying their own young after mobile, postfledging juveniles form crèches. Cliff Swallows possess a unique system of variable juvenile facial patterns, ranging from almost entirely black to almost entirely white. Interestingly, although these patterns are highly variable and distinctive in juveniles, they disappear upon maturation. We used image analysis to examine facial plumage of nestlings, and microsatellite genotyping to examine genetic relatedness among offspring within nests. We found substantial variation in facial plumage among juveniles and found a significant correlation between facial similarity and relatedness of nestlings. Genetically dissimilar juveniles in the same nest exhibited highly variable faces as measured by median pixel intensity. This variation in facial plumage may serve as a cue to allow birds to avoid misdirected parenting. We found no association between nestling relatedness and weight; this suggests that at least in the developmental period that we examined, parents may have not yet begun to use facial plumage or other cues to differentially provision offspring on the basis of genetic relatedness. If parents are able to use facial markings to distinguish between juveniles, they may do so at later stages of development, such as postfledging, to distinguish young raised in their own nest from others.